2014
DOI: 10.1016/j.algal.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria in Scandinavian coastal waters — A potential source for biofuels and fatty acids?

Abstract: Since land-based biofuel production competes with conventional food production, a water-based biomass and biofuel production from cyanobacteria offers large potential. This study investigates the application potential of cyanobacteria for fuel production and by-products by mimicking nutrient depleted environmental conditions. Three Baltic cyanobacteria strains (Aphanizomenon flos-aquae, Dolichospermum lemmermannii and Nodularia spumigena) were inoculated in full nutrient levels, as well as phosphorus and nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 82 publications
2
11
0
Order By: Relevance
“…Saturated fatty acids (SAFAs) and monounsaturated fatty acids (MUFAs) each occurred in significantly lower abundance, constituting 31.3±2.3% and 15.2±5.7%, respectively ( S3 Table ). In terms of distribution and relative abundance, the FAME content of our Dolichospermum strains is thus in good agreement with those previously reported for freshwater representatives of this genus [ 23 , 33 , 69 ] and isolates obtained from the Baltic Sea [ 67 , 70 ]. All Dolichospermum strains exclusively contained higher relative proportions of 14:0, which occurred in trace amount only in the Aphanizomenon and Nodularia strains (<1%) with the exception of Nodularia HEM, where it constituted 2.7% ( S3 Table ).…”
Section: Resultssupporting
confidence: 90%
“…Saturated fatty acids (SAFAs) and monounsaturated fatty acids (MUFAs) each occurred in significantly lower abundance, constituting 31.3±2.3% and 15.2±5.7%, respectively ( S3 Table ). In terms of distribution and relative abundance, the FAME content of our Dolichospermum strains is thus in good agreement with those previously reported for freshwater representatives of this genus [ 23 , 33 , 69 ] and isolates obtained from the Baltic Sea [ 67 , 70 ]. All Dolichospermum strains exclusively contained higher relative proportions of 14:0, which occurred in trace amount only in the Aphanizomenon and Nodularia strains (<1%) with the exception of Nodularia HEM, where it constituted 2.7% ( S3 Table ).…”
Section: Resultssupporting
confidence: 90%
“…According to their study, three Baltic cyanobacteria strains (Aphanizomenon flos-aquae, Dolichospermum lemmermannii and Nodularia spumigena) in full nutrient levels, as well as phosphorus and nitrogen depleted medium was inoculated and being monitored for 14 days. It was observed a strong negative relationship between lipid content, growth and nutrient availability, resulting in high lipid and pigment production in combination with a limited growth rate in nutrient depleted treatments (Steinhoff et al, 2014). A study carried out on different microalgae found in Mauritian marine water reported that highest amount of lipid was recorded in the Symbiodinium clade C. The presence of biodiesel was detected also by alkaline trans-esterification reaction (Keshini Beetul et al, 2014).…”
Section: Scenedesmus Obliquusysr01mentioning
confidence: 96%
“…Since landbased biofuel production competes with conventional food production, a water-based biomass and biofuel production from cyanobacteria offers large potential (Steinhoff et al, 2014). The use of lipids obtained from microalgae biomass has been described as a promising alternative for production of biodiesel to replace petro-diesel (Santos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…From the biological activity point of view, fatty acids were reported to be anticarcinogenic, antibiotic, antifungal, and antiviral (Burja et al, 2001; El-Baz et al, 2013; Table 1). Among a wide variety of fatty acids, polyunsaturated fatty acids (PUFAs) are of great concern due to their health benefits and an increasing demand in the global market (Steinhoff et al, 2014). The presence of two or more double bonds (methylene-interrupted) in fatty acids (PUFAs) makes them more valuable from nutraceutical point of view.…”
Section: An Outlook Of Metabolites: Basically What They Are?mentioning
confidence: 99%